IOT Smart Lamp Based on Arduino Using Internet Network - Agus Wiranto (LPPM Politeknik Aceh Selatan, 2025)
The development of technology in today's era is very rapid. So many innovations and many discoveries that affect everyday life make our daily lives easier and more efficient and effective, the combination of technology that we can see for example is smart home. Smart home can simply be interpreted as a smart home. Smart home can be translated as a house or building equipped with high-tech devices that allow various devices and systems to be connected to each other and is one example of technological developments that make work easier to be more efficient. From what we have discussed, here I want to make an Iot smart lamp when using electricity that can help our work more efficiently and more economically. With the progress in this era I will make a tool that makes it easy to turn off the lights with a smartphone and arduino using the XP or Extreme Programming method. Which makes it easy to turn the lights on and off using a cellphone connected using wifi without having to press the switch, just clicking on an application installed on our smartphone can turn a light on and off. .